TRANSFORMING MATHEMATICS LEARNING THROUGH GOOGLE SITES MEDIA DEVELOPMENT FOR ELEMENTARY SCHOOL STUDENTS' UNDERSTANDING AND MOTIVATION - Rahayu, Fitriya Dwi; Sulandra, I Made; Wahyuningrum, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low understanding and interest in learning mathematics among fifth grade elementary school students, especially in fractions, as indicated by numeracy achievement that is still below national standards and the dominance of conventional learning methods based on books and worksheets. The purpose of this research is to develop Google Sites-based learning media to improve students' understanding of mathematics and learning interest, and to describe the development process systematically. The method used is Research and Development (R&D) with the ADDIE model, including needs analysis, content and interface design, media development, implementation in experimental and control classes, and pretest-posttest evaluation and analysis with N-Gain. The results of the study indicate that Google Sites media is effective in improving the understanding of fraction concepts, indicated by a high N-Gain in the experimental class (0.91) compared to the control (0.30). This media also increases students' learning interest, motivation, and engagement through interactive visualizations, learning videos, quizzes, and educational games. The contribution of this research is practical and academic: practically, this media can be used as an interactive and independent learning tool; Academically, this research develops a systematic and relevant web-based learning model for the elementary school context, while also serving as a reference for the development of similar digital media.Keywords: